Impacto da percepção de risco na intenção de adoção de aplicativos de mobilidade na região metropolitana de são paulo em tempos de pandemia do COVID-19 - Joaquim Filho, José (2021)
Upon outbreak of COVID-19, government authorities have imposed protective measures to reduce exponentially increasing virus spread. Despite all government efforts, a large quantity of people still commutes every day using the already crowded mass public transport system. These travelling conditions may help spread contagious infection, thus posing risk perceptions associated to this activity in pandemic times. Numerous previous studies have shown considering behavior of individuals in society under conditions of social instability such as COVID-19 pandemic is essential both economically and sociologically. This research objective is to identify how Risk Perception in taking mass public transportation impacts behavior intention to adopt mobility application services in times of pandemic in the metropolitan region of São Paulo (RMSP). The Decomposed Theory of Planned Behavior model was used, borrowing constructs from Innovation Diffusion Theory, adding Risk Perception to the research model, applying questionnaires and statistical treatment of results by structural equations modeling (SEM). An online questionnaire was distributed from February 16 to March 5, 2021, with a total of 598 valid responses. Survey results demonstrate Compatibility and Complexity positively influence Attitude. Subjective Norms and Attitude positively influences Behavioral Intention to adopt mobility apps in the RMSP in pandemic times. Risk Perception in taking mass public transportation positively influences Subjective Norms, Attitude and Behavioral Intention. This study contributed to the theory integrating two of the most widely known theories (DTPB and IDT) and adding Risk Perception to the research model. Results confirm the appropriateness of DTPB model which has good explanatory power (R2 = 0.658) in predicting adoption intention of shared mobility applications in response to the pandemics.